2004
DOI: 10.1207/s15324834basp2601_8
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Leadership Perceptions Among African Americans

Abstract: Guided by Eagly's (1987) social role theory and Fiske's (1993) model of status effects in dyads, we studied leadership perceptions within and between gender among African American college students engaged in a problem solving task. Variance components in leadership judgments replicated the pattern of findings reported by Malloy and Janowski (1992), and extended them by showing more consensus in leadership judgments of men by both men and women. Furthermore, there was more consensus in women's judgments of men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The largest body of work to apply the SRM to zero-history groups focuses on interpersonal perceptions after minimal interaction. For instance, after only brief interactions group members were able to agree on target ratings of aggressiveness and interpersonal harm (Kenny et al, 2007; Lam, van der Vegt, Walter, & Huang, 2011), attachment (Mallinckrodt & Chen, 2004), cooperation and reliability (Greguras, Robie, & Born, 2001), effectiveness and talkativeness (Robins, Mendelsohn, Connell, & Kwan, 2004), embarrassment (Marcus, Wilson, & Miller, 1996), extroversion and conscientiousness (Campbell, Simpson, Stewart, & Manning, 2003; Levesque, 1997; Levesque & Kenny, 1993; Park & Judd, 1989; Park & Kraus, 1992), friendliness (Christensen & Kashy, 1998), hostility and submissiveness (Mallinckrodt & Chen, 2004; Marcus & Holahan, 1994), interpersonal liking (Krause, Back, Egloff, & Schmukle, 2014; Park & Flink, 1989; Sullivan & Reno, 1999; Swann, Kwan, Polzer, & Milton, 2003), leadership skills and ability (Albright & Forziati, 1995; Kenny & Livi, 2009; Kenny & Zaccaro, 1983; Livi, Kenny, Albright, & Pierro, 2008; Malloy & Janowski, 1992; Peters, Kinsey, & Malloy, 2004), levels of dominance and influence (Anderson & Kilduff, 2009; LeDoux, Gorman, & Woehr, 2012; Marcus, Lyons, & Guyton, 2000), memorability (Bond, Dorsky, & Kenny, 1992; Frey & Smith, 1993), narcissism (Küfner, Nestler, & Back, 2013; Lukowitsky & Pincus, 2013), perceived rivalry (Kenny, Kieffer, Smith, Ceplenski, & Kulo, 1996; Kilduff, Elfenbein, & Staw, 2010), self-esteem (Back et al, 2009), skill level of adolescents with learning disabilities (Scarpati, Malloy, & Fleming, 1996), social anxiety (Christensen & Stein, 2003; Marcus et al, 1996), status and power (Anderson, Srivastava, Beer, Spataro, ...…”
Section: Modeling Partner Effects In Group Researchmentioning
confidence: 99%
“…The largest body of work to apply the SRM to zero-history groups focuses on interpersonal perceptions after minimal interaction. For instance, after only brief interactions group members were able to agree on target ratings of aggressiveness and interpersonal harm (Kenny et al, 2007; Lam, van der Vegt, Walter, & Huang, 2011), attachment (Mallinckrodt & Chen, 2004), cooperation and reliability (Greguras, Robie, & Born, 2001), effectiveness and talkativeness (Robins, Mendelsohn, Connell, & Kwan, 2004), embarrassment (Marcus, Wilson, & Miller, 1996), extroversion and conscientiousness (Campbell, Simpson, Stewart, & Manning, 2003; Levesque, 1997; Levesque & Kenny, 1993; Park & Judd, 1989; Park & Kraus, 1992), friendliness (Christensen & Kashy, 1998), hostility and submissiveness (Mallinckrodt & Chen, 2004; Marcus & Holahan, 1994), interpersonal liking (Krause, Back, Egloff, & Schmukle, 2014; Park & Flink, 1989; Sullivan & Reno, 1999; Swann, Kwan, Polzer, & Milton, 2003), leadership skills and ability (Albright & Forziati, 1995; Kenny & Livi, 2009; Kenny & Zaccaro, 1983; Livi, Kenny, Albright, & Pierro, 2008; Malloy & Janowski, 1992; Peters, Kinsey, & Malloy, 2004), levels of dominance and influence (Anderson & Kilduff, 2009; LeDoux, Gorman, & Woehr, 2012; Marcus, Lyons, & Guyton, 2000), memorability (Bond, Dorsky, & Kenny, 1992; Frey & Smith, 1993), narcissism (Küfner, Nestler, & Back, 2013; Lukowitsky & Pincus, 2013), perceived rivalry (Kenny, Kieffer, Smith, Ceplenski, & Kulo, 1996; Kilduff, Elfenbein, & Staw, 2010), self-esteem (Back et al, 2009), skill level of adolescents with learning disabilities (Scarpati, Malloy, & Fleming, 1996), social anxiety (Christensen & Stein, 2003; Marcus et al, 1996), status and power (Anderson, Srivastava, Beer, Spataro, ...…”
Section: Modeling Partner Effects In Group Researchmentioning
confidence: 99%
“…However, because women are still members of a socially stigmatized group, they tend to be identified by social stereotypes. Therefore, it is possible that women may avoid leadership activities, and organizations need to recognize these social stereotypes to encourage women to take on leadership roles (Peters, Kinsey, & Malloy, 2004).…”
Section: Gender Authoritymentioning
confidence: 99%
“…Societies' gender role expectations influence an individual's leadership attitudes and beliefs (Kezar & Moriarty, 2000;Peters, Kinsey, & Malloy, 2004;Chin 2004). Studies have found that descriptors such as cooperative, participatory, interpersonal, and relationship-oriented are thought of as primarily feminine styles of leadership.…”
Section: Introductionmentioning
confidence: 99%